Transforming traditional trade of the hand-woven textile community to digital trade: The case study of Tai Lue group at Toong Mork Village, Chiang Kham, Phayao, Thailand - MUNGPATTANASUNTHON SUKAMON (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This article aims to investigate how the community of hand-woven textiles has adapted its trade to the era of disruptive technology through social media.Method: The investigations are grounded in a qualitative research approach by 1) reviewing multiple documents and literature on three aspects, namely the history of community enterprise, traditional trade, and digital trade, 2) the conceptual framework and theory of Technological Mediation, and 3) in-depth interviews via three channels: face-to-face, telephone, and social media (Line: chat application) and a site investigation approach to conduct the interviews.Findings: This study’s findings demonstrate the variety of textile patterns present in Tai Lue hand-woven culture, from the well-known Pak Wan to the lesser-known Koh pattern. Natural fabrics and those with an antique design are more costly than synthetic ones. To reach its target audience in Sibsongpanna, Southern China, the hand-woven textiles collective relies heavily on the digital trade process. After their first trip to Toong Mork with their tour guide, Sibsongpanna customers reached out to the group via social media using the Line Chat Application.Implications/Novel Contribution: Studies comparing and summarizing the process trend of digital exchange in the digital age are of interest to the hand-woven textile community. In addition, how social media has altered the daily routines and worldviews of ethnic group are fascinating to investigate.